Sistem Pendukung Keputusan Pemilihan Hero Tank Mobile Legends Terbaik dengan Metode Moora - Alterga Agus Prasetyo; Fatkhul Amin (Universitas Batanghari Jambi, 2022)
A properly made Decision Support System (DSS) will assist all communities in making effective and efficient decisions. Most people make SPK only as a recommendation for the best profession or students who have achievements, even though the DSS is very broad and can cover all aspects. Mobile Legends is a MOBA game with the Mobile genre that has many characters or heroes in the game which are divided into 6 types, one of which is the Tank type, but not all players, especially new players, know which heroes are suitable to play. Therefore, the need for an SPK for problems like this so that players don't get confused in choosing the Tank hero character and in this SPK later the user can enter any amount of data along with the value of each attribute. MOORA is one of the best methods used for DSS, MOORA has an uncomplicated calculation but produces recommendations from the best to the least recommended. Based on calculations, the best recommended Tank hero according to the Moora method is Khufra with a final value of 10.87841 while the non-recommended Tank hero is Hilda who has a final value of -2.4623.